Structural Performance Analysis of Reinforced Concrete Beams under Seismic Load - Rahmawati, Siti; Wahnich , Sophie (RESWARA: Jurnal Riset Ilmu Teknik, 2024)
The seismic performance of reinforced concrete (RC) beams is critical for structural safety in earthquake-prone regions. This study investigates the flexural and lateral behavior of RC beams under seismic loads using a combination of analytical modeling, numerical simulations, and review of contemporary literature. Finite element modeling and pushover analysis were conducted to evaluate displacement, energy dissipation, and ductility of RC beams with conventional and advanced reinforcement detailing (Opabola & Elwood, 2023; Ou et al., 2024; Zhang, 2024). Results indicate that beams with lap-spliced intermediate hoops and strong column-weak beam design significantly enhance residual drift capacity and prevent premature buckling (Sami Aljabbri et al., 2024; Sococol et al., 2022). Numerical simulations demonstrate the influence of reduced cross-sections, bond-slip mechanisms, and engineered cementitious composites on seismic response (Limin et al., 2022; Imamović & Skrinar, 2024; Xiao et al., 2018). Comparisons with experimental data validate the computational models, showing good agreement in predicting lateral displacement and energy dissipation. The study confirms that effective detailing and stiffness optimization improve the seismic resilience of RC beams, providing practical design guidance for structural engineers.